The study of knowledge, attitude and practice among diabetic patients during Ramadan at Hospital Tengku Ampuan Afzan - Che Hasan, Muhammad Kamil; Razali, Nor Razida; Md Isa, Muhammad Lokman; Ibrahim, Moustafa; Muhammad, Hussin (IIUM Press, 2021)
Background: Diabetic patients are permitted to carry out devotion of fasting by following appropriate diet regimen, medication adjustment and recommended daily physical activity. Those who do not follow the medical guideline might increase the risk for acute complication associated with fasting. This study aims to evaluate the level of knowledge, attitude, and practice among diabetic patients on fasting during Ramadan at Hospital Tengku Ampuan Afzan (HTAA). Methods: A cross-sectional study was conducted, where 62 diabetic patients were involved in this study. Convenience sampling was applied, and the study was conducted at HTAA including medical ward, orthopedic ward, surgical ward, eye ward and diabetic clinic. The data were analysis by using one-way ANOVA. Results: There were significant association between level of education factor with the attitude and practice of the diabetic patients during Ramadan with the p-value is lower than 0.05. The mean of the one-way ANOVA for attitude and practice were increased from the lowest to the highest of education level. Meanwhile, for the other sociodemographic variables (such as age, gender and receive health education), there is no significant association (p>0.05) with the level of knowledge, attitude and practice among the diabetic patients. Conclusions: The level of education showing the significant association with the attitude and practice which it implies that those have higher education background possessed better attitude and practice management of diabetic fasting during Ramadan.